Web-Based Library Information System Design at SMA S Assyfa Pasaman Barat, West Sumatra (LPPM STMIK Dharmapala Riau, 2022)
The library is a learning resource center that can support in achieving learning objectives, creating active, creative, effective, and fun learning towards quality learning. The library functions as a source of information, supporting learning for students and teachers at SMA S Assyfa West Pasaman, West Sumatra. The problem that exists is that the data collection process is still manual so that it slows down the performance of librarian in borrowing and returning books. By using the library information system design aims to maximize the performance of librarian with the help of web-based software in processing data quickly and precisely. The method used is the waterfall method with data collection techniques, namely observation and literature study. Web applications have convenience including easy access and flexibility, no need to install, fast server setup and can be updated easily. The results of this study can provide a solution to improve the service and performance of librarian in terms of managing library administrative data and speeding up transactions for borrowing and returning books by students.